For a homogeneous second order differential equation, why does a complex conjugate pair solution (m+in and m-in) to the auxiliary equation result in the complementary function y(x)=e^(mx)(Acos(nx)+Bisin(nx)), where i represents √(-1).

For a second order differential equation, our auxiliary equation, am2+bm+c=0, has two roots. Let's denote these roots as A and B. Note that A and B can be the same if there is a repeated root, but we're not considering that case here, and that A and B are not the same constants here as the ones used in the question.Now, we know that the solution to our differential equation will have the following form: y(x)=CeAx+DeBx. As we know our roots are a complex conjugate pair, we can rewrite A and B as (m+in) and (m-in), where m and n are real constants: y(x)=Ce(m+in)x+De(m-in)x=> y(x)=Cemx+inx+Demx-inx. By laws of exponents, we can rewrite y(x) as follows: y(x)=Cemxeinx+Demxe-inx. By factoring out emx, we have the following: y(x)=emx(Ceinx+De-inx). Now, by Euler's Identity, we can rewrite our einx and e-inx terms. Recalling that eikX=cos(kX)+isin(kX), we have: y(x)=emx(C[cos(nx)+isin(nx)]+D[cos(-nx)+isin(-nx)]). By distributing the constants C and D into the brackets, and recalling that cos(-X)=cos(X) (as cos(x) is an even function) and sin(-X)=-sin(X) (as sin(x) is an odd function), we find: y(x)=emx(Ccos(nx)+Cisin(nx)+Dcos(nx)-Disin(nx)) => y(x)=emx((C+D)cos(nx)+i(C-D)sin(nx)). Now, if we let C+D=A and C-D=B, where A and B are real constants, we have the following result: y(x)=emx(Acos(nx)+Bisin(nx)), as required. Note that the constants A and B here represent the constants in the question rather than the A and B used earlier in our answer.

Related Further Mathematics A Level answers

All answers ▸

A spring with a spring constant k is connected to the ceiling. First a weight of mass m is connected to the spring. Deduce the new equilibrium position of the spring, find its equation of motion and hence deduce its frequency f.


Find the general solution to the differential equation d^2x/dt^2 + 5 dx/dt + 6x = 4 e^-t


Find the vector equation of the line of intersection of the planes 2x+y-z=4 and 3x+5y+2z=13.


The complex number -2sqrt(2) + 2sqrt(6)I can be expressed in the form r*exp(iTheta), where r>0 and -pi < theta <= pi. By using the form r*exp(iTheta) solve the equation z^5 = -2sqrt(2) + 2sqrt(6)i.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences